Pengaruh Influencer Marketing, Customer Engagement Dan Content Marketing Terhadap Keputusan Pembelian Pengguna Aplikasi Shopee (Studi Pada Mahasiswa Universitas Islam Malang) - Ulumi, Ainun; Mawardi, M. Cholid; Athia, Ita (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This study aims to determine the influence of Influencer Marketing, Customer Engagement, and Content Marketing on the Purchase Decision of Shopee application users. In this digitalization era, not only has consumer interaction with products and services changed, but business strategies to reach and retain customers have also been affected. Shopee, as one of the dominant market players, continues to innovate by introducing new features such as Shopee Live, Shopee Games, and various loyalty programs to enhance customer engagement. This study employs a quantitative method with an explanatory research approach. The research population consists of students from the Islamic University of Malang who use the Shopee application, with a sample of 100 respondents selected through snowball sampling. The results show that, simultaneously, Influencer Marketing, Customer Engagement, and Content Marketing significantly influence the purchase decision of Shopee application users. Partially, Customer Engagement and Content Marketing have a positive and significant influencer on purchase decisions, while Influencer Marketing does not have a significant effect. Keywords: Influencer Marketing, Customer Engagement, Content Marketing, and Purchase Decision.